Microenvironmental control of glucose metabolism in tumors by regulation of pyruvate dehydrogenase - Golias, Tereza (Int J Cancer, 2018)
During malignant progression cancer cells undergo a series of changes, which promote their survival, invasiveness and metastatic process. One of them is a change in glucose metabolism. Unlike normal cells, which mostly rely on the tricarboxylic acid cycle (TCA), many cancer types rely on glycolysis. Pyruvate dehydrogenase complex (PDC) is the gatekeeper enzyme between these two pathways and is responsible for converting pyruvate to acetyl-CoA, which can then be processed further in the TCA cycle. Its activity is regulated by PDP (pyruvate dehydrogenase phosphatases) and PDHK (pyruvate dehydrogenase kinases). Pyruvate dehydrogenase kinase exists in 4 tissue specific isoforms (PDHK1–4), the activities of which are regulated by different factors, including hormones, hypoxia, and nutrients. PDHK1 and PDHK3 are active in the hypoxic tumor microenvironment and inhibit PDC, resulting in a decrease of mitochondrial function and activation of the glycolytic pathway. High PDHK1/3 expression is associated with worse prognosis in patients, which makes them a promising target for cancer therapy. However, a better understanding of PDC’s enzymatic regulation in vivo and of the mechanisms of PDHK-mediated malignant progression is necessary for the design of better PDHK inhibitors and the selection of patients most likely to benefit from such inhibitors.